Sistem Informasi Akuntansi Zakat, Infak Dan Sedekah - Wahid Wachyu Adi Winarto; Farah Annisa (LPPM ISNJ Bengkalis, 2020)
This research discusses the zakat, infaq and alms Accounting Information System at LAZISNU Pekalongan City. This research aims to analyze how the implementation of the Accounting Information System at LAZISNU Pekalongan City. This research is the result of field research using data collection methods through interviews, observation and documentation. The results of this study are to show the flowchart accounting system for revenue and distribution at LAZISNU Pekalongan City that has never been made by the management. Having a flowchart can help the management's performance more effectively and efficiently. There are still many people who have not put their trust in zakat management institutions as zakat distribution institutions.